Osthole Protects against Acute Lung Injury by Suppressing NF-κB-Dependent Inflammation - Yiyi Jin; Jianchang Qian; Xin Ju; Xiaodong Bao; Li Li; Suqing Zheng; Xiong Chen; Zhongxiang Xiao; Xuemei Chen; Weiwei Zhu; Weixin Li; Wencan Wu; et al. (Mediators of Inflammation)
Inflammation is a key factor in the pathogenesis of ALI. Therefore, suppression of inflammatory response could be a potential strategy to treat LPS-induced lung injury. Osthole, a natural coumarin extract, has been reported to protect against acute kidney injury through an anti-inflammatory mechanism, but its effect on ALI is poorly understood. In this study, we investigated whether osthole ameliorates inflammatory sepsis-related ALI. Results from in vitro studies indicated that osthole treatment inhibited the LPS-induced inflammatory response in mouse peritoneal macrophages through blocking the nuclear translocation of NF-κB. Consistently, the in vivo studies indicated that osthole significantly prolonged the survival of septic mice which was accompanied by inflammation suppression. In the ALI mouse model, osthole effectively inhibited the development of lung tissue injury, leukocytic recruitment, and cytokine productions, which was associated with inhibition of NF-κB nuclear translocation. These findings provide evidence that osthole was a potent inhibitor of NF-κB and inflammatory injury and suggest that it could be a promising anti-inflammatory agent for therapy of septic shock and acute lung injury.